Anastomotic stenosis following proximal gastrectomy with single flap valvulopasty successfully managed with endoscopic stricturotomy: a case report - Tian, Yuan; Shao, Qiankun; Chen, Qiang; Peng, Wei; Ren, Rui; Gong, Wei; Liu, Tianhua; Zhu, Jianhong; Wu, Yongyou (Frontiers in Surgery, 2023)
Due to its nutritional advantages over total gastrectomy (TG), proximal gastrectomy (PG) with anti-reflux techniques has attracted much attention in East Asian countries in the last few years. Double flap technique (DFT) and modified side overlap and fundoplication by Yamashita (mSOFY) are two promising anti-reflux procedures following PG. However, anastomotic stenosis after DFT and gastroesophageal reflux after mSOFY are reported with certain proportions. We designed a hybrid reconstruction procedure, namely right-sided overlap with single flap valvoplasty (ROSF), for proximal gastrectomy aiming to reduce anastomotic stricture and reflux. Among the thirty-eight patients who underwent ROSF, one patient developed Stooler grade II anastomotic stenosis. Herein, we report the successful management of this patient by endoscopic stricturotomy (ES).